Multimodal Analysis as a Basis for Studying Intonation with Expressive Value: An Approach to the Prosody-Gesture Relationship in Speech Data from Educated Speakers in Santa Clara (Islas, 2025)
Introduction: This study aims to establish a methodology for studying intonation with expressive value, grounded in the principles of the multimodal approach and its connections to Complexity Theory.Methods: The bibliographic-documentary method is employed, supported by an empirical study of spoken samples from Santa Clara, Cuba.Results: The findings demonstrate two basic principles in studying intonational meaning: 1. the intonation of a language describes acoustic patterns and features that can regularly associate with semantic-pragmatic values of expressivity; 2. interpreting these values does not always arise from the use of intonation or other prosodic features alone, but rather depends on their interaction with other verbal and nonverbal expressive means.Conclusions: The principles of the multimodal approach, in relation to Complexity Theory, should be considered as shared theoretical foundations that offer extensive possibilities for studying verbal language in connection with nonverbal means, which shape and determine the meaning of discourse units.
Keywords: multimodal analysis; intonation with expressive value; prosody-gesture relation